The Natural History of Benign Bone Tumors of the Extremities in Asymptomatic Children: A Longitudinal Radiographic Study. (7th April 2021) - Collier, Christopher D.; Nelson, Grant B.; Conry, Keegan T.; Kosmas, Christos; Getty, Patrick J.; Liu, Raymond W.
Abstract : Background: Benign bone tumors are common incidental findings in the pediatric population during radiographic evaluation. Counseling these patients requires reassurance and raises questions about the natural history of these tumors over time. The purpose of this study was to estimate the prevalence and observe the behavior of benign childhood bone tumors in an asymptomatic population. Methods: A historical, longitudinal radiographic collection of healthy children was reviewed, which included comprehensive left-sided radiographs of the extremities at yearly intervals. In this study, 262 subjects with 25, 555 radiographs were screened for benign bone tumors at a median age of 8 years (range, 0 to 18 years). All potential tumors were reviewed by a multidisciplinary panel, which confirmed the radiographic diagnosis of each lesion, the age at which the lesion first appeared, and the age at which it had resolved. Prevalence rates were calculated using the number of distinct subjects available for each radiographic location and age. Results: Thirty-five tumors were identified in 33 subjects, including 19 nonossifying fibromas, 8 enostoses, 6 osteochondromas, and 2 enchondromas. The prevalence rate for all tumors combined increased with age and was 18.9% overall. The overall prevalence rates for specific tumor types were 7.5% for nonossifying fibromas, 5.2% for enostoses, 4.5% for osteochondromas, and 1.8% for enchondromas. Nonossifying fibromas demonstrated a bimodal distribution of prevalence, with a peak at 5 years (10.8%) and another after skeletal maturity (13.3%). The median age at the first appearance for all tumors combined was 9 years (range, 2 to 15 years), but varied by tumor type. Nonossifying fibromas often resolved (7 [37%] of 19), with further resolution possible beyond the last available radiograph. Enostoses, osteochondromas, and enchondromas persisted until the last available radiographs in all subjects. Conclusions: The prevalence of benign childhood bone tumors of the extremities was 18.9% in a historical asymptomatic population. Longitudinal radiographs allowed observation of the timing of the first appearance and the potential for resolution for each tumor type. These findings provide unique evidence to answer many commonly encountered questions when counseling patients and their families on benign bone tumors. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.